5-Hydroxymethylcytosine discriminates between parathyroid adenoma and carcinoma. Issue 1 (December 2016) - Barazeghi, Elham; Gill, Anthony; Sidhu, Stan; Norlén, Olov; Dina, Roberto; Palazzo, F.; Hellman, Per; Stålberg, Peter; Westin, Gunnar
Abstract Background Primary hyperparathyroidism is characterized by enlarged parathyroid glands due to an adenoma (80–85 %) or multiglandular disease (~15 %) causing hypersecretion of parathyroid hormone (PTH) and generally hypercalcemia. Parathyroid cancer is rare (<1–5 %). The epigenetic mark 5-hydroxymethylcytosine (5hmC) is reduced in various cancers, and this may involve reduced expression of the ten-eleven translocation 1 (TET1) enzyme. Here, we have performed novel experiments to determine the 5hmC level and TET1 protein expression in 43 parathyroid adenomas (PAs) and 17 parathyroid carcinomas (PCs) from patients who had local invasion or metastases and to address a potential growth regulatory role of TET1. Results The global 5hmC level was determined by a semi-quantitative DNA immune-dot blot assay in a smaller number of tumors. The global 5hmC level was reduced in nine PCs and 15 PAs compared to four normal tissue samples (p  < 0.05), and it was most severely reduced in the PCs. By immunohistochemistry, all 17 PCs stained negatively for 5hmC and TET1 showed negative or variably heterogeneous staining for the majority. All 43 PAs displayed positive 5hmC staining, and a similar aberrant staining pattern of 5hmC and TET1 was seen in about half of the PAs. Western blotting analysis of two PCs and nine PAs showed variable TET1 protein expression levels. A significantly higher tumor weight was associated to PAs displaying a more severe aberrant staining pattern of 5hmC and TET1. Overexpression of TET1 in a colony forming assay inhibited parathyroid tumor cell growth. Conclusions 5hmC can discriminate between PAs and PCs. Whether 5hmC represents a novel marker for malignancy warrants further analysis in additional parathyroid tumor cohorts. The results support a growth regulatory role of TET1 in parathyroid tissue.